Proceedings of the 3rd International Conference on Banking, Accounting, Management and Economics (ICOBAME 2020) 2020
DOI: 10.2991/aebmr.k.210311.078
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Pentagon Fraud in Detecting Fraudulent Financial Reporting: Using the Beneish Model in Manufacturing Companies on the Indonesia Stock Exchange

Abstract: This study aims to analyze the effect of pressure, opportunity, rationalization, capability, arrogance on fraudulent financial reporting. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange. The results showed that financial stability pressures, industrial conditions had a positive and significant effect on fraudulent financial reporting, while the change of directors had a significant negative effect on fraudulent financial reporting. Financial stability pressures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Fraud is known as the action taken by a company that causes misstatements in the financial statements to obtain a higher profit. Elaboration of the studies of the fraud determinants has been carried out from year to year (Utomo, 2018;Farmashinta & The effect of real earnings management, fraud, and earnings informativeness … Journal of Accounting andInvestment, 2023 | 540 Yudowati, 2019;Septriani & Desi Handayani, 2018;Yesiariani & Rahayu, 2017;Nugroho et al, 2021). Based on several studies, it is concluded that two factors that always affect fraud are external pressure and financial stability (Firmansyah et al, 2022).…”
Section: H 1c : Earnings Management Under Discretionary Costs Has a N...mentioning
confidence: 99%
“…Fraud is known as the action taken by a company that causes misstatements in the financial statements to obtain a higher profit. Elaboration of the studies of the fraud determinants has been carried out from year to year (Utomo, 2018;Farmashinta & The effect of real earnings management, fraud, and earnings informativeness … Journal of Accounting andInvestment, 2023 | 540 Yudowati, 2019;Septriani & Desi Handayani, 2018;Yesiariani & Rahayu, 2017;Nugroho et al, 2021). Based on several studies, it is concluded that two factors that always affect fraud are external pressure and financial stability (Firmansyah et al, 2022).…”
Section: H 1c : Earnings Management Under Discretionary Costs Has a N...mentioning
confidence: 99%